Addressing Malnutrition Across the Continuum of Care: Which Patients Are Likely to Receive Oral Nutritional Supplements - Graham, Jove; Fan, Linlin; S. Meadows, Eric; Hang, Lillian; Partridge, Jamie; Goates, Scott (Journal of Aging Research And Healthcare, 2017)
Oral nutritional supplements (ONS) have been shown to improve patient outcomes in the hospital setting, but limited results from long-term care or community settings exist. Using electronic health records (EHRs) from 2009 to 2014 for both adult inpatients and outpatients, we compare the demographic and clinical characteristics of patients who received ONS (n = 1,251) with a non-ONS control group (n =25,513). Multivariable logistic regression modeling was used to describe and compare differences in baseline characteristics between the groups including age, sex, race, tobacco use, and comorbidities. We found that patients receiving ONS were older and sicker than control patients. Hospitalized ONS patients were more likely to be admitted from the emergency department and have a hospitalization within the last month prior to the index date. Our results suggest that there is a need for nutrition screening and incorporating nutrition status into the EHR as an important way to coordinate hospital and community medical care. ONS can be an important therapy for vulnerable populations in both the hospital and the community settings.
Keywords: Oral Nutritional Supplements; Care Continuum; Malnutrition; Electronic Health Records; Outpatient